Socioecological Profile of Active Adults. Sport as a Whole-life Choice - Biernat Elżbieta; Skrok Łukasz; Majcherek Dawid; Nałęcz Hanna (Sciendo, 2020)
Hitherto empirical research provides insight on particular dimensions or aspects thereof, but analyses that include diverse determinants of the physical activity are scarcer. The aim of the research was to examine the profile of adults who engage in sport activity, using a multi-layer, socio-ecological approach. Combined database: The Social Diagnosis 2015, The Statistics Poland 2014, and the Orliki 2012 was applied. The resulting sample consists of 8,361 adult respondents aged 25-70 years. Sport activity and sport clubs' membership were measured as dependent variables. According to the Bronfenbrenner's layered model number of outcome variables were described. While being consistent with fundamental facts known from the literature (e.g. significance of age, education, family, social networks and cultural aspects, the results point to a heterogeneity in determining sport activity. Firstly, women and men differ qualitatively - the set of characteristics important for sport activity is different. For example, while minor health issues seem to instigate activity of women, for men they are rather negatively related. Secondly, different factors are relevant for initiating the activity than for sustaining it. Furthermore, sport activity is rather positively related to other activities related to social life or to the life-long learning. This suggests that a substitution effect, in terms of time, is less important than the general tendency to be engaged in different aspects of life. Lastly, active membership of sports clubs is not only rare, but also qualitatively differs from sports activity in terms of socio-ecological profile of the participants. The obtained results emphasize the need to create and implement nuanced and varied policies to support increase in physical activity in modern societies. Traditional, 'hard' measures like providing physical (facilities) or organisational (sports clubs) infrastructure seem to have limited effectiveness.